A fish for a friend - Muhammad Khairulnizam Kader (Nanyang Technological University, 2021)
This report will be covering the workin whichthe filmA Fish for a Friend underwent, and technical and artistic issues faced in ensuring that the film was able to be produced. Being a project,which are handled by a total of six people,this report would be zeroinginon the production, and post-productionaspect of the project, mainly the modelling, lighting,and rendering, as well as the compositing part of the project.